Validitas Modul Pembelajaran IPA Berorientasi Konstruktivisme Bermuatan Pendidikan Karakter Untuk Siswa Kelas VIII SMP - Karlini Oktarina (BULLET : Jurnal Multidisiplin Ilmu, 2025)
Referring to primary data collected through observation and interview to natural science teachers and some students, it is found that there is no natural science teaching materials in the form of learning modules that can make learners learn independently, build their own knowledge, and construct good character in themselves. In order to address this problem, then it is developed natural science learning module oriented to constructivism with the contain of character education. The purpose of this study is to reconstruct valid module of natural science learning materials. This type of research is a development research using the Plomp model. The development phase of the Plomp model consists of 3 stages, namely 1) preliminary research phase, 2) development or prototyping phase, and 3) assessment phase. The result of the study shows that natural science learning module oriented to constructivism with the contain of character education for students class VIII of Yunior High School is strongly valid. In future work, practicality and effectiveness will be investigated.